2001
DOI: 10.1074/jbc.m006073200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Phospholipase C β2-Binding Site Near the Amino-terminal Coiled-coil of G Protein βγ Subunits

Abstract: In previous work (Sankaran, B., Osterhout, J., Wu, D., and Smrcka, A. V. (1998) J. Biol. Chem. 273, 7148 -7154), we showed that overlapping peptides, N20K (Asn 564 -Lys 583 ) and E20K (Glu 574 -Lys 593 ), from the catalytic domain of phospholipase C (PLC) ␤2 block G␤␥-dependent activation of PLC ␤2. The peptides could also be directly cross-linked to ␤␥ subunits with a heterobifunctional cross-linker succinimidyl 4-[N-maleimidomethyl]-cyclohexane-1-carboxylate. Cross-linking of peptides to G␤ 1 was inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…The current data with AGS8 in both the yeast and mammalian systems along with the recent reports regarding direct regulation of G␤␥ (27,28) and diversity of G␤␥ binding partners (29,30) suggest that G␤␥ may possess additional protein binding sites for signal processing (28,31). Such G␤␥ binding partners may serve as effectors for mammalian G␤␥, influence receptor coupling to G␣␤␥ or localize G␤␥ within a larger signaling complex, where it can regulate specific signaling pathways independent of the classical heterotrimeric G␣␤␥.…”
Section: Resultsmentioning
confidence: 99%
“…The current data with AGS8 in both the yeast and mammalian systems along with the recent reports regarding direct regulation of G␤␥ (27,28) and diversity of G␤␥ binding partners (29,30) suggest that G␤␥ may possess additional protein binding sites for signal processing (28,31). Such G␤␥ binding partners may serve as effectors for mammalian G␤␥, influence receptor coupling to G␣␤␥ or localize G␤␥ within a larger signaling complex, where it can regulate specific signaling pathways independent of the classical heterotrimeric G␣␤␥.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has found that G␤␥ contains multiple binding sites for PLC␤2. In addition to the G␣ contact surface, the N-terminal coiled coil domain and the outer surface of the G␤ are also involved in binding PLC␤2 (22,31). In the absence of other constraints, G␤␥ activates PLC␤2 primarily through the G␣ t contact region (26).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, by swapping the PH domain of PLC-β2 into the remainder of PLC-δ1, we obtained a chimera that binds non-specifically to membranes like PLC-β2, and moreover, binds and is responsive to Gβγ subunits [72]. In two distinct studies, it was found that the N-terminal region of PLC-β3 encompassing the PH domain and a part of the EF-hands region binds to Gβγ [73] whereas it was reported that Gβγ helps the recruitment of a GFP-tagged PH-β1 on subcellular membranes [74] Additionally, an independent series of studies located a solvent-accessible segment of nine residues (574-583 segment) in the Y region that is able to bind to Gβ [71,[75][76][77]. This segment, although partially-conserved in PLC-δ1, could govern the oscillation of the PLC-β2 between two distinct parts of Gβ subunit to be distal or proximal to the membrane surface [71].…”
Section: Gβγ Binding Site(s) In Plc-β2mentioning
confidence: 99%
“…Comparing a model structure of PH-β2 with the known structure of PH-δ1 suggests that the β5/β6 loop, which is longer than in PH-δ1, (Figure 3) could act as a regulatory domain for activation by Gβγ [41]. A peptide corresponding to this loop (PHβ [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] ) activates the enzyme, and this activation is competitive with Gβγ activation. The structure of PLC-β2 reveals that the β5/β6 loop does not belong to the surface that is tightly packed with the EF-hands and the catalytic regions, or to the hydrophobic ridge interacting with Rac2.…”
Section: Role Of the Ph Domain In Plc-δ1 And Plc-β2 Activationmentioning
confidence: 99%
See 1 more Smart Citation